2012
DOI: 10.1161/atvbaha.111.244731
|View full text |Cite
|
Sign up to set email alerts
|

BAFF Receptor Deficiency Reduces the Development of Atherosclerosis in Mice—Brief Report

Abstract: Objective-The goal of this study was to assess the role of B-cell activating factor (BAFF) receptor in B-cell regulation of atherosclerosis. Methods and Results-Male LDL receptor-deficient mice (Ldlr −/− ) were lethally irradiated and reconstituted with either wild type or BAFF receptor (BAFF-R)-deficient bone marrow. After 4 weeks of recovery, mice were put on a high-fat diet for 6 or 8 weeks. BAFF-R deficiency in bone marrow cells led to a marked reduction of conventional mature B2 cells but did not affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 19 publications
9
120
1
1
Order By: Relevance
“…However, bone marrow transfer also induces some changes in the B cell compartment, for example, in the balance between B1a and B1b cells in the periphery. Nevertheless, similar and corroborating findings from bone marrow transplant and nonbone marrow transplant studies involving B cells 29,30 suggest this model continues to provide valuable information. Future studies are required to understand the specific contribution of CD4+ T cells and the relative atheroprotective contributions of antibody binding to oxLDL versus secondary necrotic cells.…”
Section: 44supporting
confidence: 54%
See 1 more Smart Citation
“…However, bone marrow transfer also induces some changes in the B cell compartment, for example, in the balance between B1a and B1b cells in the periphery. Nevertheless, similar and corroborating findings from bone marrow transplant and nonbone marrow transplant studies involving B cells 29,30 suggest this model continues to provide valuable information. Future studies are required to understand the specific contribution of CD4+ T cells and the relative atheroprotective contributions of antibody binding to oxLDL versus secondary necrotic cells.…”
Section: 44supporting
confidence: 54%
“…[25][26][27] We and others have shown follicular B2 cell interactions with CD4 + T cells, antagonized by marginal zone B2 cells, promote pathogenic T cell responses in the atherosclerotic setting. [28][29][30][31][32][33] Few models have, therefore, addressed the specific role of antibodies in isolation without impacting on other B cell functions. Altogether, it is hard to predict the …”
Section: Meet the First Author See P 198mentioning
confidence: 99%
“…Deletion of the BAFF receptor (BAFFR), necessary for B2 development, was also recently shown to be protective in at least two studies (968,1528). Like the anti-CD20 antibody infusion studies, BAFFR deficiency resulted in marked selective reduction of B2 cells with little effect on B1a cells.…”
Section: The Atherogenic Effect Of Igg Appears To Depend On the Targetmentioning
confidence: 99%
“…On the other hand, use of anti-CD20 to deplete B-2 cells in mice, which spared B-1 cells in the peritoneum, reduced atherosclerosis, as well as activation and proliferation of DCs and CD4 + T cells, suggesting that B-2 cells were proatherogenic by several mechanisms (60,94). Furthermore B cell-activating factor receptor (BAFF-R) deficiency, which causes a reduction in B-2 but not B-1 cells, also reduced lesion development and macrophage and T cell infiltration (95,96). However, recent data demonstrated a role for the Id3-CCR6 pathway in mediating aortic B cell homing, and demonstrated that resident adventitial B cells mediated protection from early atherosclerosis in part through inhibiting intimal macrophage accumulation (97).…”
Section: B Cells and Ab Responses In Atherosclerosis B-1 Cells And Igmentioning
confidence: 99%